A retrospective case series evaluating the outcome of implants with low primary stability. Issue 9 (24th June 2019) - Lee, Kwan‐Joo; Cha, Jae‐Kook; Sanz‐Martin, Ignacio; Sanz, Mariano; Jung, Ui‐Won
Abstract: Objectives: There is a need of more studies on whether low primary implant stability would negatively influence the success of implant therapy. Therefore, this retrospective study analyses outcomes of implants placed with low primary stability and factors that may be related to implant failures. Material and methods: This retrospective study included 156 patients, restored with 169 implants that presented manual rotation within an observed follow‐up time of a minimum of 34 days and a maximum of 9.28 years. Descriptive statistics, survival analyses (life tables and Kaplan–Meier estimates) and radiographic assessment based on marginal bone level measurements were performed. This original study was adherent to STROBE guidelines. Results: Seven implants failed in seven patients, rendering cumulative survival rates of 94.74% (95% CI: 89.11–97.50) and 94.33% (95% CI: 88.30–97.30) at implant and patient levels, respectively. Kaplan–Meier estimates showed implant loss was found only in advanced surgery group (7 implant loss in 82 implants) when compared with simple surgery group (no implant loss in 87 implants; p = 0.005). Conclusions: Within the limitations of this retrospective study, implant placement with low primary stability might not negatively affect either the survival rates or marginal bone level changes of implants provided that a protected and unloaded healing is guaranteed.